Dose Optimization With Pituitary Gland Hormone For Induced Breeding Of Bata Fish (Labeo Bata) (Bangladesh Journal of Animal Science, 2012)
An experiment on induced breeding of bata fish (Labeo bata) was carried out to determine the optimum dose of pituitary gland hormone. The present study consisted of four treatments namely TI, T2, T3, and T4 with three replications of each. Twenty-four pairs of male and twelve pairs of female were selected from the brood rearing ponds and the average body wt of the female and male were 390±10 and 258±9 g respectively. To observe the effective dose for induced breeding, the females were first injected at the rate of 0.5 (T1), 1.0 (T2), 1.5 (T3) and 2.0 (T4) mg PG/kg body wt. while the second doses were performed at the rate of 4.0 (T1), 4.5 (T2), 5.0 (T3), and 5.5 (T4) mg PG/kg body wt. after 6 h from the first dose. On the other hand the males were administered a single dose of 2 mg PG/kg body wt. at the time of second dose of the female. The ovulation rate, fertilization rate, hatching rate and survival rate were determined. Among the four treatments T2 (1.0 mg PG/ kg body wt.) showed the best result in terms of ovulation rate (89%), fertilization rate (84%), hatching rate (85%) and survival rate (84%). The dose of 1.0 mg PG/kg body wt. can be used in induced breeding of bata fish (L. bata) for the development of hatchery propagation. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9871 BJAS 2008; 37(1): 70-77